A knockin mouse model for human ATP4a(R703C) mutation identified in familial gastric neuroendocrine tumors recapitulates the premalignant condition of the human disease and suggests new therapeutic strategies - Calvete, Oriol (Dis Model Mech, 2016)
By whole exome sequencing, we recently identified a missense mutation (p.R703C) in the human ATP4a gene, which encodes the proton pump responsible for gastric acidification. This mutation causes an aggressive familial type I gastric neuroendocrine tumor in homozygous individuals. Affected individuals show an early onset of the disease, characterized by gastric hypoacidity, hypergastrinemia, iron-deficiency anemia, gastric intestinal metaplasia and, in one case, an associated gastric adenocarcinoma. Total gastrectomy was performed as the definitive treatment in all affected individuals. We now describe the generation and characterization of a knockin mouse model for the ATP4a(R703C) mutation to better understand the tumorigenesis process. Homozygous mice recapitulated most of the phenotypical alterations that were observed in human individuals, strongly suggesting that this mutation is the primary alteration responsible for disease development. Homozygous mice developed premalignant condition with severe hyperplasia, dysplasia and glandular metaplasia in the stomach. Interestingly, gastric acidification in homozygous mice, induced by treatment with 3% HCl acid in the drinking water, prevented (if treated from birth) or partially reverted (if treated during adulthood) the development of glandular metaplasia and dysplasia in the stomach and partially rescued the abnormal biochemical parameters. We therefore suggest that, in this model, achlorhydria contributes to tumorigenesis to a greater extent than hypergastrinemia. Furthermore, our mouse model represents a unique and novel tool for studying the pathologies associated with disturbances in gastric acid secretion.